ANALISIS PERBANDINGAN KINERJA KEUANGAN PADA PERUSAHAAN SUB SEKTOR SEMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA (STUDI KASUS PADA PT. INDOCEMENT TUNGGAL PRAKARSA, TBK DAN PT. SEMEN INDONESIA, TBK ) - Anjani, Putri; Munandar, Aris (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2024)
This research aims to determine whether there are differences in financial performance in cement sub-sector companies listed on the Indonesia Stock Exchange (case study of PT. Indocement Tunggal Prakarsa, Tbk and PT. Semen Indonesia, Tbk) seen from the Current Ratio (CR), Debt ratios. To Equity Ratio (DER) and Net Profit Margin (NPM). The research instrument used in this research is a table listing the Current Ratio (CR) variable indicators, namely current assets and current debt, the Debt To Equity Ratio (DER) variable indicators, namely total debt and total equity and the Net Profit Margin (NPM) variable indicator which contains net profit and sales at PT. Indocement Tunggal Prakarsa, Tbk and PT. Semen Indonesia, Tbk. The population used is all profit and loss financial report data in the form of sales or income, profit after tax and profit before tax from the company PT. Indocement Tunggal Prakarsa, Tbk and PT. Semen Indonesia, Tbk with the sampling technique used in this research is purposive sampling. Data was collected by means of documentation and literature study then analyzed using an independent sample t test. The research results show that there are differences in the financial performance of PT. Indocement Tunggal Prakarsa, Tbk and PT. Semen Indonesia, Tbk when viewed from the Current Ratio (CR), Debt To Equity Ratio (DER).